2020
DOI: 10.21037/apm-20-625
|View full text |Cite
|
Sign up to set email alerts
|

Experimental vascular protective shield combined with vacuum sealing drainage prevents pressure on exposed vessels and accelerates wound repair

Abstract: Background: The sustained negative pressure created by vacuum sealing drainage (VSD) on exposed vascular wounds can result in blood vessel compression, embolism, or necrosis. The objective of this research was to explore the ability of an experimental vascular protective shield combined with VSD to protect exposed vessels of the lower limbs and accelerate wound repair.Methods: (I) The vascular protective shield was prepared; (II) the material was subjected to acute toxicity and hemolysis tests; (III) and 30 Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, clinically, it is worth noting that because of the complexity of the soft‐tissue wound, such as the irregular shape and different depths of the wound, the application of VSD is prone to a situation where the material is not fully applied to the wound and the wound is difficult to seal. Furthermore, it was reported that the combination of an experimental vascular protective shield with VSD could reduce influences on systolic and diastolic capacities of the myocardium and avoid multiple compressions of exposed vessels, thus contributing to early vascularisation of wounds and wound repair 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinically, it is worth noting that because of the complexity of the soft‐tissue wound, such as the irregular shape and different depths of the wound, the application of VSD is prone to a situation where the material is not fully applied to the wound and the wound is difficult to seal. Furthermore, it was reported that the combination of an experimental vascular protective shield with VSD could reduce influences on systolic and diastolic capacities of the myocardium and avoid multiple compressions of exposed vessels, thus contributing to early vascularisation of wounds and wound repair 29 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that the combination of an experimental vascular protective shield with VSD could reduce influences on systolic and diastolic capacities of the myocardium and avoid multiple compressions of exposed vessels, thus contributing to early vascularisation of wounds and wound repair. 29 …”
Section: Discussionmentioning
confidence: 99%
“…We previously reported improvement of wound healing by NPWT after surgical treatment, including skin grafts 4,5 . The effects of NPWT include physical contraction of the wound, removal of edema from the wound bed, maintenance of a moist wound environment, induction of cytokines, and promotion of angiogenesis 6,7 . However, the precise mechanisms responsible for the improvement in wound healing by negative pressure remain largely unknown.…”
mentioning
confidence: 99%